The Level of Green Manufacturing Implementation Using SWOT Analysis in The Local Garment Creative Industry in Bandar Lampung - Hasiany, Sillak; Setiajaya, Arif; Alifa, Nabila Putriyandri; Putri, Intan Andriani; Zulaicha, Anissaa Siti (Penerbit Kemala Indonesia, 2024)
The garment industry dominates the micro, small, and medium-sized enterprises (MSMEs) in Lampung Province after the culinary industry. One of the products of the garment industry is batik, whose manufacturing processes can produce hazardous waste for the environment if they are not properly managed. The negative impact can be minimized through the implementation of Green Manufacturing. This study was conducted to measure the level of green manufacturing implementation using Key Performance Indicator (KPI) matrix that has been tested and modified from Supply Chain Operation Reference (SCOR) matrix. The KPI matrix comprises the planning, procurement, and manufacturing processes. This research also aims to provide alternative strategy recommendations to improve the implementation of green manufacturing in Batik XYZ in Lampung Province. The average value of the green manufacturing implementation in Batik XYZ is 52.7, indicating that Batik XYZ falls into the average category.. Based on the SWOT analysis, the recommended strategy is W - T (Weakness - Threat), which is to start a comprehensive evaluation of water and electricity usage efficiency in the production process, inspection and recording of the existing company's production waste output, and to practice proper waste management.